Pengaruh Kerapatan Gulma terhadap Pertumbuhan Odot (Pennisetum purpurem Cv. Mott) untuk Pakan Ternak - Defri Taruna; Adhona Bhajana Wijaya Negara (Pusat riset dan Inovasi Nasional, 2025)
Odot grass (Pennisetum purpureum cv. Mott) is widely recognized as a high-yielding and nutrient-rich forage crop, making it suitable for feeding ruminant animals. This study investigates how varying levels of weed density affect the growth performance and fresh forage yield of odot grass. The experimental design employed was a non-factorial Randomized Block Design (RBD) with four weed density treatments (0%, 35%, 70%, and 100%) and six replications for each treatment. Growth indicators measured included plant height, number of tillers, stem thickness, and total fresh biomass production. The results showed that weed density significantly influenced all measured parameters (p < 0.05). The absence of weeds yielded the highest forage production (19.32 tons per hectare), whereas full weed coverage (100%) led to a substantial reduction in yield by 15.53%. A strong inverse correlation was observed between weed density and forage yield, with a correlation coefficient of r = –0.97. These findings suggest that higher weed densities substantially hinder both the vegetative growth and biomass output of odot grass. Nevertheless, a moderate weed presence (35%) did not cause a statistically significant decrease in productivity, indicating a potential threshold for acceptable weed competition.